Materiał szkieletowy z katedry gnieźnieńskiej (X/XI - XVII wiek) - Kaszycka, Katarzyna A. (Polskie Towarzystwo Antropologiczne, 1987)
A cranio- and osteometric analysis was made of skeletons excavacated form the basement of the Cathedral since 1957. Basic statistical characteristics of selected metrical traits were presented. A comparative analysis was conducted between the Gniezno series and other mediaeval Polish series.
Skeletal material from the Gniezno cathedral (10 th - 17 th centuries)